Acute severe thrombocytopenia after treatment with ReoPro (abciximab). Issue 4 (1st April 2000) - Butler, R; Hubner, P J B
Abstract : ReoPro (abciximab) is an extremely potent inhibitor of the glycoprotein IIb/IIIa receptor, the final common pathway of platelet activation and aggregation. Its main role is the maintenance of coronary patency after suboptimal results with coronary intervention. However, one of the complications of this treatment is excessive bleeding, a problem which may be compounded by a rare idiosyncratic thrombocytopenic reaction. A severe episode of thrombocytopenia in a 64 year old man is described; he was treated with ReoPro for a right coronary stenosis which had not been resolved by angioplasty. His platelet level dropped quickly and only improved after 20 units of platelets were given.